Implikasi Kebijakan TKDN terhadap Minat dan Kinerja Emiten Asing di Sektor Teknologi dalam Pasar Modal Indonesia - Muhammad Alldo Hibahtillah; Sang Ayu Putu Rahayu; Duhita Driyah Suprapti (Media Hukum Indonesia (MHI), 2026)
Factually, the implementation of the Domestic Component Level (TKDN) policy in Indonesia creates various implications for foreign technology issuers in the Indonesian capital market, both as an opportunity and a challenge. This study aims to analyze the legal framework governing TKDN policies and examine their implications for the interest and performance of foreign issuers in the technology sector within the Indonesian capital market. This research employs a normative juridical method with statutory and conceptual approaches through the analysis of primary and secondary legal materials. The results indicate that TKDN policy has been regulated through several laws and regulations, including Law Number 3 of 2014 concerning Industry and various ministerial regulations related to domestic component requirements in the technology sector. The policy is intended to strengthen domestic industries, encourage technology transfer, and increase the competitiveness of local products. However, in practice, the implementation of TKDN policies may influence the attractiveness of Indonesia’s capital market for foreign technology issuers due to regulatory complexity, compliance costs, and limitations in domestic industrial capacity.